Literature Review: Application of Gamification in Puzzle-Assisted Chemistry Learning on the Periodic System of Elements - Daulay, Rabiah Afifah; Khairiansyah, Azli; Ramadhani, Abidah; Yurinda, Aisya; Marsyah, Aralia Putri; Chandra, Yogi (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research explores the use of gamification in chemistry education by incorporating puzzles into the study of the Periodic System of Elements. Gamification, which integrates game-like elements into non-gaming contexts, aims to boost students' motivation and improve their academic performance. In chemistry learning, gamification can transform the educational experience into a more engaging and stimulating one, particularly for challenging subjects like the Periodic System of Elements. Puzzles serve as a gamification tool that can enhance students' interest and facilitate a better understanding of complex chemistry concepts through interactive engagement. The study utilizes a literature review approach to gather and analyze various relevant articles, revealing that puzzle-based learning can enhance student participation, alleviate anxiety, and promote teamwork. The results suggest that employing gamification through puzzles not only deepens students' comprehension of fundamental chemical principles but also cultivates a favorable attitude towards learning chemistry. Consequently, the use of puzzles in gamification is recommended as a valuable and enjoyable educational strategy.